Vascularized dental pulp regeneration using cell-laden microfiber aggregates. Issue 48 (2nd December 2022) - Liang, Qingqing; Liang, Cheng; Liu, Xiaojing; Xing, Xiaotao; Ma, Shixing; Huang, Haisen; Liang, Chao; Liu, Lei; Liao, Li; Tian, Weidong
Abstract : Schematic illustration of cell-laden microfiber aggregates for pulp regeneration. (A) The fabrication process of DPSC-laden and HUVEC-laden microfibers. (B) Cell-laden microfiber aggregates were filled into tooth roots for ectopic pulp regeneration. Abstract : Regeneration of dental pulp via the transplantation of dental pulp stem cells (DPSCs) has emerged as a novel therapy for dental pulp necrosis after inflammation and injury. However, providing sufficient oxygen and nutrients to support stem cell survival, self-renewal, and differentiation in the narrow root canal remains a great challenge. In this study, we explored a novel strategy based on cell-laden microfibers for dental pulp regeneration. Firstly, we fabricated suitable GelMA hydrogels that facilitate the survival and proliferation of DPSCs and human umbilical vein endothelial cells (HUVECs) and possess satisfactory biomechanical properties to generate microfibers. Two kinds of GelMA microfibers were fabricated with DPSCs and HUVECs via a silicone-tube-based coagulant bath-free method. Live/dead and Ki-67 immunofluorescence staining assays identified that these two cell lines maintained high survival rate and proliferation ability in GelMA microfibers. Immunofluorescence staining confirmed that DPSCs fully spread in the microfibers and highly expressed CD90 and laminin. HUVECs positively express CD31 and VE-cad in microfibers and could migrate well in the GelMA hydrogel. In vitro permeation experiments confirmed the superiority of microfiber aggregates (MAs) in liquid permeation compared to GelMA hydrogel blocks. We further adopted an ectopic pulp regeneration assay in nude mice to validate the regeneration of the aggregates of mixed DPSC-microfibers and HUVEC-microfibers in vivo . Compared to a conventional mixture of DPSCs and HUVECs in GelMA hydrogel blocks, the aggregates of cell-laden microfibers generated more pulp-like tissue, blood vessels, and odontoblast-like cells that positively express DMP-1 and DSPP. To our knowledge, this is the first attempt to apply cell-laden MAs for pulp regeneration. Our study proposes a new solution to the challenge of pulp regeneration, which might promote the clinical translation and application of stem cell-based therapy.